Assessment of brace types of performance and optimal bracing configuration on steel frames structures - David Dominguez-Santos; Pedro Muñoz Velasco (Informes de la Construccion)
The structural behavior of steel has deficiencies such as buckling, due to the thinness of the steel profiles in relation to their length. Commonly, this problem is solved by introducing bracing elements and shear walls. However, this effect also depends on the location of the braces in the structures. In this work, the optimal position of the braces in an eight-story frame is evaluated, analyzing 16 different situations in terms of resistance, ductility, and displacements, using static (Push-over) and dynamic (Time-history) methods with the registration from Lorca. The conclusions obtained in this work have been to determine the importance of ductile solutions in the structures and the use of bracing on all floors of the porch with symmetrical arrangements in height.